دور ممارسة الأنشطة البدنية و الرياضية في تنمية بعض القيم الأخلاقية - كروم, بشيــر; النحوي, الطاهر (Université de M'sila, 2015)
تهدف مؤسسـات التربية والتعليم إلى تحقيق النمو الأمثل للتلميذ من جميع النواحي البدنية والمهارية والذهنية والوجدانية، بما يكفل تكوين الشخصـية المتزنة المتكاملة التي تستطيع أن تُكيِّف نفسها للحياة في المجتمع، وأن تساهم في تدعيم هذا المجتمع وتنميته. و التربية البدنية تقوم بدور واضـح في تدعيم الدوافع وتثبيتها لدى الممارسين، فالإنسـان يتشـكل ويتطور أثناء الممارسـة الرياضية، ويكسـب منها طابعاً مميزاً حيث الاحتياج إلى التعاون والتسامح والإحترام والصـبرو الصدق و الأمانة و الشجاعة و التواضع وتحمل المسـؤولية و حسن الخلق و حب الآخرين وغيرها من السـمات الأساسية الضرورية لممارسة الأنشطة الرياضية سواءً الجماعية منها أو الفردية. فالتربية البدنية بتنوع أنشـطتها التي توفِّر فرص المواقف السلوكية المختلفة يمكنها بالتوجيه أن تدعم هذا السـلوك الذي يتماشى مع القيم الخُلقية التي يدين بها المجتمع وتمنع السلوك الذي يتعارض معها. و هذا ما يدفعنا الى القيام بهذه الدراسة التي سنحاول من خلالها الوقوف على درجة تنمية ممارسة الأنشطة البدنية و الرياضية لبعض القيم الأخلاقية لدى تلاميذ المرحلة الثانوية من وجهة نظر أساتذة المادة منطلقين من التساؤل التالي: ما درجة تنمية ممارسة الأنشطة البدنية و الرياضية لبعض القيم الأخلاقية لدى تلاميذ المرحلة الثانوية ؟ Summary of intervention Education institutions designed to achieve optimal growth of the pupil of the all-round physical and skill, mental and emotional, so as to ensure balanced integrated personality that can adapt themselves to life in the community composition, and contribute to the strengthening and development of this society. And physical education are a clear role to play in strengthening the motives and install the practitioners, man is formed and evolved during sports practice, and earns them a distinctive character where the need for cooperation and tolerance, respect and Alsbero honesty and Secretariat and the courage and humility, responsibility and good manners and love others and other basic features necessary for sports activities, whether individual or collective ones. Education is the diversity of physical activities that provide opportunities for various behavioral attitudes could guidance to support this behavior, which is in line with moral values owed by the society and prevent behavior which conflicts with it. And this is what motivates us to do this study, which we will try to stand on the degree of development of the practice of physical activities and sports for some moral values among high school students from the perspective of professors article departing from the following question: What degree of development of the practice of physical activities and sports for some moral values among high school students?
Keywords: ممارسة الأنشطة البدنية و الرياضية تنمية بعض القيم الأخلاقية